2017
DOI: 10.1016/j.bjid.2017.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Unrecognized pediatric and adult family members of children with acute brucellosis

Abstract: The routine screening of both pediatric and adult family members of index cases is a priority in endemic areas. Using this screening approach, unrecognized family members who are seropositive for brucellosis will be identified earlier and be able to receive prompt treatment.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
10
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(12 citation statements)
references
References 14 publications
(22 reference statements)
1
10
0
1
Order By: Relevance
“…Due to the common living area and the common food consumption, the risk of Brucella is increased in family members of index case family members. In previous studies, with the scanning of family members, the seropositivity rate was reported as 9.5% -36.8% and it was suggested that family members should be examined for Brucella [16,17]. In our study, brucella history rate of patients' family members was found to be 39.2%.…”
Section: Discussionsupporting
confidence: 50%
“…Due to the common living area and the common food consumption, the risk of Brucella is increased in family members of index case family members. In previous studies, with the scanning of family members, the seropositivity rate was reported as 9.5% -36.8% and it was suggested that family members should be examined for Brucella [16,17]. In our study, brucella history rate of patients' family members was found to be 39.2%.…”
Section: Discussionsupporting
confidence: 50%
“…Brucellosis confronts public health currently as a widespread problem all over the world and it is especially common in the Middle East including Turkey [1][2]. The incidence of this zoonotic disease in Turkey is around 23-25 per 100,000 annually [1,3]. Brucellosis is frequent in the rural areas of Turkey, especially in Central and Southeastern Anatolia, where animal husbandry is common.…”
Section: Introductionmentioning
confidence: 99%
“…Brucellosis is frequent in the rural areas of Turkey, especially in Central and Southeastern Anatolia, where animal husbandry is common. Among the causative strains, Brucella melitensis is the most commonly isolated strain [1,3].…”
Section: Introductionmentioning
confidence: 99%
“…Direct contact with infected animal is a possible acquision route of infection in older children whose families are engaged in animal husbandry. 1,13 The majority of our patients had a history for consumption of unpasteurized milk, suggesting that this was the most common route of acquisition in this setting. Although human to human transmission is rare, cases of neonatal infection have raised the possibility of transplacental transmission.…”
Section: Discussionmentioning
confidence: 95%